THE IMPLEMENTATION OF COLLABORATIVE WRITING METHOD FOR WRITING INSTRUCTION IN THE ENGLISH EDUCATION STUDY PROGRAM - Setio Wati, Ning (JURNAL PEDAGOGY, 2013)
Abstract : Collaborative writing is not a new methodology in teaching of English as Foreign Language (EFL). It has been adopted in many countries in recent years. This article reviews the application of collaborative writing method to teach writing skill at the college level. Because many researchers appear to believe students can be taught to collaborate, they urge educators to provide explicit instruction that encourages development of skills such as coordination, communication, conflict resolution, decision-making, problem-solving, and negotiation. This article also expands the operational definition of collaborative writing in process of writing instruction. Then, it tries to discuss the procedures of writing instruction using collaborative writing method. The last, this article describes the benefits of collaborative writing method in the classroom.Â Key Words: Collaborative Writing, Writing, EFL